Modelling the cost-effectiveness of cancer prevention : reframing models to better match policy questions - O'Mahony, James F. (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2013)
This thesis comprises six papers concerning methodological issues in cost- effectiveness analysis (CEA) of healthcare interventions. The unifying theme to these studies is the reframing of CEAs to better correspond to the policy questions they are to inform. The first two papers concern the differential discounting of costs and effects in CEA. Differential discounting is the application of a different discount rate to costs and health effects, as distinct from the more usual practice of applying a common discount rate to both. Differential discounting has been advocated as a means of making CEA models more representative of reality, as it accounts for anticipated growth in the value of health over time. What has not been anticipated by advocates of differential discounting are its implications for models featuring multiple fiature cohorts that start an intervention after the discount year. This leads to the systematic improvement of cost-effectiveness ratios when future cohorts are added to a CEA model. The first paper describes this problem and explains why it leads to difficulties when comparing cost-effectiveness estimates between studies. It uses a CEA of vaccination against the human papillomavirus (HPV) to illustrate the effect of adding multiple future cohorts to an analysis.
Keywords: Histopathology, Ph.D.; Ph.D. Trinity College Dublin